PEMODELAN ANOMALI GRAVITASI SESAR DENGAN PENDEKATAN MODEL SHEET (MODELLING GRAVITY ANOMALIES OF FAULT BY SHEET MODEL APPROACH) - Nurwidyanto, M Irham; Setiawan, Ari (BERKALA FISIKA, 2011)
AbstractThe modelling gravity anomaly of fault model with a model sheet approach with the aim toÂ study the response of gravity anomalies of faults was done.Modelling is done by modelling approaches bedding with a thickness t and density contrastwith surrounding Î”Ï. The Â gravity anomaly at a point are formulated and Â the calculation andvisualization program created in matlab8RS.Â From the modelling is made it can be concluded that the fault position is generally locatedbetween the gravity anomaly minimum and maximum gravity anomaly. When thetypes of fault arevertical normal fault then the fault position precisely located on the horizontal gradient Â maximumvalue, whereas when the fault are not vertical, the location of fault are Â to be near (around) themaximum horizontal gradient.Key words: modelling, gravity anomalies, faults, model sheets.